The Effect of Brand Ambassador, Brand Image, Brand Trust and E- WOM on Purchase Intention for Halal Skincare Product. (Study on Avoskin Skincare in Surabaya) - Fatkhiyatus Sa’adah; Rachma Rizqina Mardhotillah (Journal of Halal Research, Policy, and Industry, 2023)
The development of the skincare industry has made the competition in the cosmetics industry even tighter. Skincare is one of the favorite things for women. Many skincare brands in the local cosmetic industry launch a lot of new skincare products to compete for customers, making consumers very careful when buying skin care products. Existing competition requires local skincare to be aggressive in innovating in order to keep pace with foreign products entering Indonesia. One of the innovations that have been made is to make a series of products more specific than before. This study aims to analyze the influence of brand ambassadors, brand image, brand trust and e-wom on purchase intention of Avoskin skincare products. The research method uses a quantitative method with a purposive sampling technique. The distribution of questionnaires was made online via Google forms which were distributed to 260 respondents within four days. Analysis of this research using SPSS. The results of this study are that there is a positive and significant influence between brand trust and e-wom on purchase intention. However, in this study it was found that brand ambassadors did not have a positive and significant influence on purchase intention and brand image also had a positive and insignificant influence on purchase intention.